2022
DOI: 10.3390/plants11233239
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine Ammonia Lyase GmPAL1.1 Promotes Seed Vigor under High-Temperature and -Humidity Stress and Enhances Seed Germination under Salt and Drought Stress in Transgenic Arabidopsis

Abstract: Seed vigor is an important agronomic attribute, essentially associated with crop yield. High-temperature and humidity (HTH) stress directly affects seed development of plants, resulting in the decrease of seed vigor. Therefore, it is particularly important to discover HTH-tolerant genes related to seed vigor. Phenylalanine ammonia lyase (PAL, EC 4.3.1.24) is the first rate-limiting enzyme in the phenylpropanoid biosynthesis pathway and a key enzyme involved in plant growth and development and environmental ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Several studies have reported a similar increase in water solubility index (WSI) with germination time. Zhang et al [29] observed this increase in germinated rice our. Another study reported increase in WSI due to the increase in water soluble albumins observed previously in germinating oats and barley [34,35].…”
Section: Ash Contentmentioning
confidence: 57%
See 1 more Smart Citation
“…Several studies have reported a similar increase in water solubility index (WSI) with germination time. Zhang et al [29] observed this increase in germinated rice our. Another study reported increase in WSI due to the increase in water soluble albumins observed previously in germinating oats and barley [34,35].…”
Section: Ash Contentmentioning
confidence: 57%
“…The enzyme esterase is responsible for cleaving the chemical bonds that bind phenolic compounds, resulting in the release of these compounds [28]. Zhang et al [29] reported the activation of phenylalanine ammonia-lyase, a key enzyme in phenolic biosynthesis, during seed germination. Each experiment was carried out in triplicate and data were reported as means ± standard deviation (SD).…”
Section: Ash Contentmentioning
confidence: 99%
“…Studies have shown that upregulation of PAL , C4H , and 4CL in plants can increase plant tolerance to biotic or abiotic stress [ 49 , 50 ]. Among them, overexpression of PAL has been proven to reduce the level of ROS in Arabidopsis seeds and leaves, increase the activity of POD, CAT, and the content of flavonoids, and reduce the accumulation of MDA [ 51 ]. In this study, the relative concentration of p -coumaric acid and 4-hydroxystyrene increased dramatically under p -CA stress but dropped significantly with BDO particle additions.…”
Section: Discussionmentioning
confidence: 99%
“…Salt stress will have a severe toxic effect on each growth stage of soybean plants, which will eventually leading to the loss of soybean yield and the reduction of soybean quality [ 51 , 52 , 53 ]. Predecessors studied the molecular mechanisms of soybean salt tolerance, and some genes were identified such as GmPAL1.1 , GmCHX1 , GmSALT3 , GmHKT1;4 , and GmbZIP44 [ 54 , 55 , 56 , 57 , 58 ]. Meanwhile, the molecular mechanism of soybean GSTs under salt stress has not been thoroughly studied and identified.…”
Section: Introductionmentioning
confidence: 99%